Application of fast technology for analysis (FTA) for sampling and recovery of deoxyribonucleic acid (DNA) for molecular characterization of cowpea breeding lines for Striga resistance - Omoigui, L.O.; Ishiyaku, M.F.; Ousmane, B.; Gowda, B.S.; Timko, M.P. (Academic Journals, 2011)
Striga gesnerioides (Willd) Vatke is a significant constraint to cowpea production in the dry savannas of sub-Saharan Africa. Yield losses caused by S. gesnerioides in these regions are estimated in millions of tons annually and the prevalence of Striga soil infestation is steadily increasing. Conventional breeding efforts have developed some cowpea lines with Striga resistance as well as other important agronomic traits but it is time-consuming and difficult to pyramid favorable traits. The use of marker-assisted selection (MAS) makes it easier to select plant traits and reduce the time needed to develop new varieties. The potential of Fast Technology for Analysis (FTA) as an effective technology for sampling and retrieval of DNA from plant tissue and their subsequent molecular analysis was assessed in the laboratory. DNA was successfully recovered from the leaf tissues of cowpea pressed into the FTA® Classic card and the DNA obtained from the FTA papers was found to be suitable for molecular analysis by PCR-based techniques. The marker efficiency of Sequence Characterized Amplified Region (SCAR) marker MahSe2 and C42B was 93% in detecting SG3 resistance. This study demonstrated that the application of MAS using FTA technology has the potential to put the breeding process on a fast track and increase the efficiency of breeding activities.